Spatial age-period-cohort analysis of hepatitis B risk in Xinjiang from 2006 to 2019 - Wang, Yijia; Xie, Na; Li, Fengjun; Wang, Zhe; Ding, Shuzhen; Hu, Xijian; Wang, Kai (Frontiers in Public Health, 2023)
Objective To understand the spatio-temporal distribution and epidemiological characteristics of hepatitis B risk in 96 districts and counties of Xinjiang to provide relevant reference for the prevention and treatment of hepatitis B. Methods Based on the incidence data of hepatitis B in 96 districts and counties of Xinjiang from 2006 to 2019, the change characteristics of the disease in the spatial region were analyzed in the global trend, and the spatial clustering of hepatitis B was discussed by the methods of spatial autocorrelation and spatio-temporal clustering analysis to identify the high-risk clustering regions and time periods. The integrated nested Laplace approximation(INLA)-based spatial APC model was established to further explore the influence of age, period, birth queue effect and spatial distribution on the incidence risk of hepatitis B, and sum-to-zero constraint was adopted to avoid the problem of model unrecognition. Results The risk of hepatitis B in Xinjiang is increasing from east to west and from south to north, with spatial heterogeneity, and spatio-temporal scanning statistics yielded five clustering areas.The spatial APC model showed two peaks in the average risk of hepatitis B, at [25,30) years old and [50,55) years old respectively. The average incidence risk of hepatitis B fluctuated around 1 with the passage of time, and the average risk of disease by birth cohort displayed a trend of increasing first, then decreasing and finally stabilizing. Taking age, period and cohort effect into consideration, it is found that the areas with high risk of hepatitis B are Tianshan District, Xinshi District, Shuimogou District, Changji city, Aksu City, Kashi City, Korla City, Qiemo County and Yopurga County in northern Xinjiang. According to the time-space effect item, it was found that there are unobserved variables affecting the incidence of hepatitis B in some districts and counties of Xinjiang. Conclusion The high-risk population and spatio-temporal characteristics of hepatitis B disease required attention. It is suggested that the relevant disease prevention and control centers should strengthen the prevention and control of hepatitis B among young people, while paying attention to the middle-aged and elderly people, and strengthen the prevention and monitoring of high-risk areas.